Analisa Kinerja Persimpangan Tak Bersinyal Di Kota Pagar Alam - Dyan Pratnamas; Herwin Herwin (JURNAL ILMIAH BERING'S, 2016)
Transport is an essential part of a functioning society life in this era of increasingly majau. Transport very close relationship with the lifestyles, interests and needs of the productive activities to meet all needs. To meet the needs of transportation, the need to hold a transport planning process, particularly for urban transport often creates parking, riders, and the increasing number of road users are some of the causes that can lead to increased delays traffic flow at intersections, reduced road capacity and increase the number of Linta accidents in several intersections.